Looking at b-learning and online experience in higher education during COVID-19 - Casquilho-Martins, I.; Belchior-Rocha, H.; Miguel, L. (EDULEARN21 - 13th annual International Conference on Education and New Learning Technologies, 2021)
COVID-19 caused changes in teaching practices at various levels of education, namely in higher education. This study aims to present an analysis of an experience with higher education students in a b-learning pedagogical model, before and during the current pandemic and in different moments of the confinement measures. The curricular unit analyzed started with a blended-learning approach since 2018, considering the importance of innovative pedagogical models in student learning and became an essential resource during the pandemic period. This case study was composed of a sample of 269 students from a Portuguese public University who attended the curricular unit Methods and Study Techniques, as optional, in their 1st year of degree, between February 2018 and March 2021.The data were processed using SPSS v.27, seeking to analyze different moments, according to the different confinement measures decreed by the Portuguese Government. Participants are aged between 17 and 64 years old, 62.5% female and 24.5% worker-students. It was found that regardless of the context of confinement, students showed positive satisfaction with the online course, with its contents, with the platform and with the b-learning pedagogical method, especially during total confinement when classes were in distance learning. The most valued aspects in this modality were the flexibility of teaching the curricular unit and time management. The acquired tools were highly valued by the students, first for the adaptability that gave them, but mainly to face the distance learning challenge in their 1st year of degree, giving them planning and organizing skills for autonomous work. Most students did not point out a disadvantage in this modality, although they expressed the importance of face-to-face classes that were suspended in the context of a pandemic.